2017
DOI: 10.1016/j.fitote.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Flavonolignan 2,3-dehydrosilydianin activates Nrf2 and upregulates NAD(P)H:quinone oxidoreductase 1 in Hepa1c1c7 cells

Abstract: Silybum marianum (milk thistle) is a medicinal plant used for the treatment of various liver disorders. This study examined whether the main flavonolignans from S. marianum (i.e. silybin, silychristin, silydianin) and their 2,3-dehydro derivatives (i.e. 2,3-dehydrosilybin, 2,3-dehydrosilychristin, 2,3-dehydrosilydianin) activate the Nrf2 pathway, which regulates the expression of genes encoding many cytoprotective enzymes, including NAD(P)H:quinone oxidoreductase 1 (NQO1). After 48 h of exposure, 2,3-dehydrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 34 publications
1
17
2
Order By: Relevance
“…While silybin A, silybin B and silychristin A were quite weak chelators, 2,3-dehydrosilybin was found to be a potent iron and copper chelating agent [10]. Moreover, 2,3-dehydrosilydianin (but not silybin, silychristin, silydianin, 2,3-dehydrosilybin, or 2,3-dehydrosilychristin) was found to activate Nrf2 and upregulate NAD(P)H:quinone oxidoreductase 1 in Hepa1c1c7 cells [11]. 2,3-Dehydrosilybin and its gallates were also more efficient inhibitors of angiogenesis that silybin and silybin derived gallates [12,13].…”
Section: Resultsmentioning
confidence: 97%
“…While silybin A, silybin B and silychristin A were quite weak chelators, 2,3-dehydrosilybin was found to be a potent iron and copper chelating agent [10]. Moreover, 2,3-dehydrosilydianin (but not silybin, silychristin, silydianin, 2,3-dehydrosilybin, or 2,3-dehydrosilychristin) was found to activate Nrf2 and upregulate NAD(P)H:quinone oxidoreductase 1 in Hepa1c1c7 cells [11]. 2,3-Dehydrosilybin and its gallates were also more efficient inhibitors of angiogenesis that silybin and silybin derived gallates [12,13].…”
Section: Resultsmentioning
confidence: 97%
“…In current investigations, SM and its flavolignans have shown to activate Nrf2 (Table 1). The research of Roubalová et al [151] found that, after h of exposure of the main Silybum marianum flavolingnans and their 2,3-dehydroderivatives, 25 µM and 50 µM of 2,3-dehydrosolydianin significantly increased the activation of Nrf2 and the expression of the Nqo1 gene, 1.6-and 2.3-fold, respectively, as well as of the target genes Hem oxygenase1 (Hmox-1), gammaglutamyl-cystein ligase modifier subunit (Gclm), and gamma glutamyl-cystein ligase catalytic subunit (Gclc) by 2.2-fold, 1.5-fold, and 1-3-fold, respectively, but only at a concentration of 50 µM against the control in murine Hepatoma Hepa1c1c7 cells. In addition, the concentration of NOQ1 and GCLM proteins also increased at 50 µM, whereas the levels of HMOX1 and GCLC did not change significantly.…”
Section: Nrf2 Activated By Silymarin and Flavolignans: Promising Thermentioning
confidence: 99%
“…Blood urea nitrogen (BUN) was measured using a commercial kit (BUN II reagent kit; Wako Pure Chemical Industries). [16] Biochemical estimation of serum lipid profile Triglycerides, total cholesterol, HDL-cholesterol and LDL-cholesterol concentrations were evaluated enzymatically using assay kits (Sigma Chemical Co, St Louis, MO, USA). Very low-density lipoprotein (VLDL)-cholesterol was calculated as triglycerides and LDL-cholester-ol was calculated by the equation LDL-cholesterol=Total serum cholesterol -(HDL+VlDl).…”
Section: Biochemical Estimation Of Serum Urea Creatinine and Bunmentioning
confidence: 99%